x(3x-2)=

Simple and best practice solution for x(3x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(3x-2)= equation:


Simplifying
x(3x + -2) = 0

Reorder the terms:
x(-2 + 3x) = 0
(-2 * x + 3x * x) = 0
(-2x + 3x2) = 0

Solving
-2x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-2 + 3x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-2 + 3x)' equal to zero and attempt to solve: Simplifying -2 + 3x = 0 Solving -2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 0 + 2 3x = 0 + 2 Combine like terms: 0 + 2 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667

Solution

x = {0, 0.6666666667}

See similar equations:

| 2-5x=-2x+11 | | x^6-48=0 | | 12z+12y+13z-y= | | N+4n=30 | | 4+4n=-12+2 | | w/2-3(12)=53 | | 8cos^2(x)+4cos(x)-1=0 | | -3x+9=6 | | 16-x/5=x/3 | | 4x(3+x)=16+x | | 6x-5-2x=3y+7-4x | | 7.2a=13.53+2.81a | | y-12=3y-2 | | .12a-.08b=0 | | 5n/3-3/7=61/21 | | 20m+12n-5m+13n+65= | | 5/r-9=8/r+5 | | 4x-24=4x+60 | | 6w-14=4w+24 | | 7x-1=-85 | | 6w-14=4w | | 1/2(2x+54)=1/3(9x+27) | | w/2-3(6)=53 | | 6/7x-3=45 | | (4x+3)/9-(2x+1)/2=0 | | 35+0.10p=25+0.25p | | 0.023X+0.08=0.36X-5.266 | | 35p+0.10=25p+0.25 | | 13b+9-12c= | | 8=g/7 | | 180=2x+(x-8)+x | | -2/5r+2r=1/5r+14/3 |

Equations solver categories